Volume 4: 20th International Conference on Design Theory and Methodology; Second International Conference on Micro- And Nanosys 2008
DOI: 10.1115/detc2008-49383
|View full text |Cite
|
Sign up to set email alerts
|

Design Team Framing: Paths and Principles

Abstract: This paper addresses two major challenges new product development teams face in making a product people want. The first challenge is to frame the design situation based on a real need of a customer. The second challenge is to get everyone on the team in agreement about what that framing is — everyone needs to be on the same page about what it is they’re doing. Yet these two challenges are not independent, they are intertwined with each other, connected by the concrete research and sharing activities the teams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Corrections regarding finite slit height [29] , Zeeman effect and Fine-structure are applied [2,21,22] during the analysis process and thus accounted for regarding the resulting temperatures and velocities. Corrections regarding CXRS cross-sections are negligible due to the low temperatures and perpendicular viewing angle [43].…”
Section: Accuraciesmentioning
confidence: 99%
“…Corrections regarding finite slit height [29] , Zeeman effect and Fine-structure are applied [2,21,22] during the analysis process and thus accounted for regarding the resulting temperatures and velocities. Corrections regarding CXRS cross-sections are negligible due to the low temperatures and perpendicular viewing angle [43].…”
Section: Accuraciesmentioning
confidence: 99%
“…This led to an increase group rapport and better results. Other researchers also showed that discussions play an important role and teams that synthesize their knowledge into a shared understanding tend to have more successful design processes and outcomes [13,15]. Our research seeks to embody these findings into computational support for data synthesis.…”
Section: Background and Related Workmentioning
confidence: 88%
“…Filtering, organizing and making sense of uncertain and ambiguous information is complicated and exhausting [13,20]. Teamwork can help support this critical phase of the design process, but it also introduces the difficulty of creating a common ground and making decisions that all team members support [14].…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations